Electrophysiological Mechanisms Underlying T-Wave Alternans and Their Role in Arrhythmogenesis - You, Tingting; Luo, Cunjin; Zhang, Kevin; Zhang, Henggui (Frontiers in Physiology, 2021)
T-wave alternans (TWA) reflects every-other-beat alterations of morphology on the electrocardiogram (ECG) ST segment or T wave in the setting of a constant heart rate, hence, in the absence of heart rate variability. It is proved to be associated with dispersion of repolarization, and used as a noninvasive marker for predicting the risk of malignant cardiac arrhythmias and sudden cardiac death as numerous studies have shown. The aim of this review is to provide up-to-date information associated with possible mechanisms underlying the genesis of TWA at the cellular level, the genesis of spatial concordant/discordant alternans at the tissue level and their transition to cardiac arrhythmia, which are unveiled by both experimental and simulation studies. Recent progress and future perspectives in antiarrhythmic therapies associated with TWA are also discussed.